Comparative Failure Analysis of PLA, PLA/GNP and PLA/CNT-COOH Biodegradable Nanocomposites thin Films. (2015) - Pinto, V.C.; Ramos, Tiago; Alves, Sofia; Xavier, J.; Tavares, Paulo; Moreira, P.M.G.P.; Guedes, Rui Miranda
Abstract: Biodegradable polymers such as poly(lactic) acid (PLA) have been studied for biomaterials applications such as natural human ligament replacement, however these materials could be applied to other sectors as aerospace, aeronautics, automotive, food packaging. PLA presents a relatively brittle with a mode I fracture behavior, being often blend with other biodegradable or non-degradable polymers to improve its fracture energy. For some existing applications, PLA components exhibit accumulated permanent deformation resulting from dynamic mechanical inputs, resulting on failure by laxity of parts. Aiming the improvement of PLA mechanical properties, the inclusion of carbon nanofillers into PLA matrix, in particular, CNT-COOH and GNP have been developed, due to their strong sp 2 carbon-carbon bondings and their geometric arrangement that enhance mechanical properties of the polymer matrix. PLA and nanocomposites were produced by melt blending followed by compression molding in a hot press, with small weight percentages of nanofillers added to the matrix. Quasi static tensile tests were performed on a mechanical testing machine (Instron™ ElectroPuls E1000) along with failure analysis of specimens with centered crack with digital image correlation, revealing strain distribution along specimens.